MAXIMIZING FINANCIAL POTENTIAL: THE SHARIAH ECONOMICS APPROACH TO TIME VALUE IN FINANCIAL MANAGEMENT - Nur, Fatiha; Miftah, Surur (LPPM STAI Muhammadiyah Probolinggo, 2025)
The concept of Time Value of Money (TVM) in conventional economics assumes that money has a higher value today compared to the future due to the potential earnings through interest. However, this principle contradicts the values in Islamic economics, which prohibit the practice of riba (interest). This article aims to explore the Islamic economic approach to TVM and analyze how Islamic principles can be applied in modern financial management. This study uses a qualitative descriptive approach with a literature review, examining the Qur'an, Hadith, and relevant fatwas, as well as academic literature on Islamic economics and financial instruments such as mudharabah, musyarakah, and murabahah. The findings show that Islam views money as a medium of exchange that should not be traded for profit without real productive activity. Islam encourages the use of financial instruments based on real assets and fair risk-sharing, with principles such as al-kharaj bi al-dhaman and al-ghunmu bi al-ghurmi. This approach emphasizes the value of benefits and contributions to the real economy, rather than interest calculations or speculation. The study concludes that applying Islamic principles in modern financial management can create a more just, sustainable financial system oriented towards the welfare of the community, while also reducing social and economic inequality.